Life Cycle Assessment of Electricity Generation Systems in Angola - Filemon, André; Tembo, André; Cabenda, Manuel; Malaca, Sulemane; Barros, António André Chivanga (International Journal of Energy Economics and Policy, 2025)
Many countries are actively engaged in transforming and diversifying their electrical systems, adopting regulations that promote the integration of renewable energy sources. This process, often referred to as the energy transition, aims to significantly reduce CO2 emissions, enhance energy efficiency by 2030, and mitigate the impacts of climate change. Temporal assessments of energy transformations provide critical insights into the consumption capacity and potential of primary energy sources. These evaluations enable the identification and prediction of future trends, offering a framework to understand the consequences and opportunities associated with energy transitions. Such insights facilitate the maximization of positive outcomes while minimizing or mitigating adverse effects. This study aims to assess the impact of energy sustainability in Angola’s electrical system by considering social, environmental, and economic dimensions. The methodology utilized in this work is based on a life cycle assessment (LCA) approach to evaluate Angola’s energy system comprehensively. This includes all stages, from primary energy sources to the final disposal phase, represented by CO2 emissions. Computational tools for LCA were employed to process data and generate detailed results. The analysis facilitated the identification of trends within the energy sector, enabling the development of strategic recommendations to improve the efficiency and sustainability of Angola’s energy infrastructure, with a focus on enhancing the electrical grid and its associated systems. The study results reveal critical trends in Angola’s energy sector, highlighting areas for improvement in efficiency and sustainability across the energy value chain. Strategic recommendations were developed to optimize Angola’s energy infrastructure, emphasizing advancements in the design, operation, and modernization of the country’s electrical grid and associated systems. These improvements aim to reduce environmental impacts, enhance energy reliability, and support the transition to a more sustainable and resilient energy framework. Thus, the sustainability of Angola’s electricity system was evaluated from social, environmental, and economic perspectives, leveraging Life Cycle Analysis to consider every stage—from primary energy sources to generation, transportation, distribution, and final disposal—highlighting the CO2 emissions that contribute to climate change.